2018
DOI: 10.3889/oamjms.2018.313
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of Moringa Oleifera Role on Gut Microbiota Composition and Inflammation Associated with Obesity Following High Fat Diet Feeding

Abstract: AIM:The alteration in the gut microbial community has been regarded as one of the main factors related to obesity and metabolic disorders. To date, little is known about Moringa oleifera as a nutritional intervention to modulate the microbiota imbalance associated with obesity. Therefore we aim to explore the role of aqueous Moringa oleiferous leaf extract on Lactobacilli and Bifidobacteria in high-fat diet-induced obesity and to investigate whether any restoration in the number of caecal Lactobacilli and Bifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…The Proteobacteria phylum is a marker of gut dysbiosis [ 68 ], and one of the phyla increased along the axis. It has been associated with a high-fat diet and obesity in mice [ 69 ], with consumption of animal fat [ 70 ], and most importantly, with a colonic mucosa more easily penetrated by other bacteria [ 71 ]. This may explain the low abundance observed in MD, where animal fat consumption is greatly diminished, but not in PD, which includes several animal-derived products.…”
Section: Discussionmentioning
confidence: 99%
“…The Proteobacteria phylum is a marker of gut dysbiosis [ 68 ], and one of the phyla increased along the axis. It has been associated with a high-fat diet and obesity in mice [ 69 ], with consumption of animal fat [ 70 ], and most importantly, with a colonic mucosa more easily penetrated by other bacteria [ 71 ]. This may explain the low abundance observed in MD, where animal fat consumption is greatly diminished, but not in PD, which includes several animal-derived products.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera leaf extract in a study showed that it could serve as a gut modulator in obesity‑induced dysbiosis, thus proving a significant correlation between increased levels of bifidobacteria and reduced leakiness in the gut. [ 23 ]…”
Section: Outcomes and Discussionmentioning
confidence: 99%
“…Diet ( 139 , 140 ) has shown to be closely associated with the composition and diversity of gut microbiota ( Figure 2 ). De Filippo et al once conducted a study that aimed to find whether there are some differences between the gut microbiota of children (BF) fed with traditional rural African diet, characterized with low in fat and animal protein and rich in starch, fiber, and plant polysaccharide and children (EU) eating a typical western diet high in animal protein, sugar, starch, and fat and low in fiber.…”
Section: Therapymentioning
confidence: 99%